Interaksi Teman Sejawat Dan Aktivitas Berorganisasi Terhadap Sikap Berwirausaha Pada Himpunan Mahasiswa Program Studi Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta Angkatan 2013 - Novitasari, Isnaini; , Dr. Wafrotur Rohmah M.M (2016)
This study aimed to analyze the influence of peer interaction and organizational activity attitude towards entrepreneurship. The sample in this study was 165 member student organization Student Association Program (HMP) in FKIP Muhammadiyah University of Surakarta in 2013. The data analysis technique used is multiple linear regression, t-test, F, Effective and Relative Contribution. Based on the survey results revealed that there is significant influence caused by the interaction of peers on attitudes to entrepreneurship 49.5% Effective Contribution; There is a significant effect caused by the activity of organizing the entrepreneurship attitude 4.7% Effective Donation. There is a significant effect arising from the interaction of peers and organize activities together against the attitude of the student entrepreneurship organization members Student Association Program (HMP) in FKIP Muhammadiyah University of Surakarta in 2013. Keywords: interaction of peers, organize activities, attitudes to entrepreneurship